La cultura en Cuba y en el mundo: “Americanidad” and “Cubanidad” in Alejo Carpentier - Martínez Rodríguez, Dianelkys (2022)
La cultura en Cuba y en el mundo (2003), is a book that brings together conferences by Alejo Carpentier, from 1964 to 1966. The purpose of the article is to detect the meanings of Americanidad and Cubanidad in this work, in addition to exposing the findings of a criticism reading that allowed the identification of its biographical meaning, visualization of sociological relations and its link to the cultural policy of the Cuban Revolution. Carpentier’s discourse was organized from the logic between narrative-music and the universal, particular and singular philosophical approach, where there are similar characteristics such as: the theory of contexts, epic, real, marvelous, baroque, time, use of words and folkloric. In addition, the emergence of a creator-anthropologist is recognized, which originates a national and political consciousness of the intelligentsia. In a general, it is concluded that “americanidad” and “cubanidad” express a national identity arising from the Conquest and colonization.